Compact, High‐resolution Inverse‐Designed On‐Chip Spectrometer Based on Tailored Disorder Modes. Issue 9 (9th July 2021) - Hadibrata, Wisnu; Noh, Heeso; Wei, Heming; Krishnaswamy, Sridhar; Aydin, Koray
Abstract: Integrated optical sensors have garnered much interest for lab‐on‐chip applications such as chemical and biological sensing and detection. Among various ways for detection schemes, spectral analysis performed by a spectrometer has shown great promise. Typically, such spectrometry is carried out in a relatively large device, owing to the fact that spectral resolution is often dictated by large optical path length. Here, a high‐resolution compact spectrometer utilizing random scattering events in a disordered medium is demonstrated. The spectrometer is inverse designed by objective‐first method and fabricated using two‐photon polymerization technique. The compact spectrometer consists of a disordered photonic structure and an inversed‐designed mode decomposer. A spectral resolution of 0.25 nm with a bandwidth of 30 nm in the near‐infrared regime is realized from a spectrometer occupying a relatively small footprint of 30 × 12.8 µm 2 . The proposed platform has a great potential to be used as a versatile lightweight and compact spectrometer for various applications including on‐chip spectrometer and sensing. Abstract : A high‐resolution compact spectrometer utilizing random scattering events in a disordered medium is demonstrated. The compact spectrometer consists of a disordered photonic structure and an inversed‐designed mode decomposer. A spectral resolution of 0.25 nm with a bandwidth of 30 nm in the near‐infrared regime is realized from a spectrometer occupying a relatively small footprint of 30 x 12.8 µm 2 .